Orientasi Baru Lingkungan Pendidikan - Singgih Aji Purnomo (STIT Muslim Asia Afrika, 2021)
This paper aims to uncover a new educational environment. Using a phenomenological approach, this paper is expected to have a new perspective in the form of an introduction to the educational environment that arises as a result of pandemic conditions covid-19. The results were concluded that two new environments emerged, namely the personal environment and the virtual environment.